INFLUENCE OF RESOURCES AVAILABILITY AS A TRAUMA MANAGEMENT APPROACH ON PERFORMANCE OF NATIONAL POLICE SERVICE PROJECTS IN NYERI COUNTY, KENYA - Irungu, Alice Wanjiku; Dr Anthony Wainaina Ndungu, (IJRDO - Journal of Social Science and Humanities Research, 2021)
The purpose of this study was to assess the influence of resources availability on performance of   national police service projects in Nyeri county, Kenya. The objectives of this research was to; establish the influence of Human Resources availability on performance of national police service projects in Nyeri county, Kenya, to investigate the influence of Technological Resources on performance of national police service projects in Nyeri county, Kenya and; to evaluate the influence of Material Resources on performance of national police service projects in Nyeri county, Kenya. The research employed descriptive research design to obtain data; Convenience sampling technique was utilized to draw a sample of 76 respondents from 104 Kenya police and administration police officers in Nyeri central police station. In addition, a structured interview was conducted on 8 purposeful selected OCS, OCPD, County Commander, and Sub-County commanders for interview. Descriptive statistics and inferential statistics were the statistics produced. The specific descriptive statistics included frequencies, means, and standard deviations, and was presented in the form of frequency tables and a multiple linear regression model. Data from the study was edited, coded and analyzed using Statistical Package for Social Sciences (SPSS). Content analysis was used to analyze qualitative data, while descriptive statistics was used to analyze quantitative data. Raw data drawn from the responded questionnaires was ran through Statistical Package for Social Science (SPSS version 22.0) software for analytical purpose. The study established that human resources availability has a profound effect on psychological aspect that have a far-reaching impact on performance of national police service projects, that technological resources availability influences performance of national police service projects and that availability of money or material resources aids in meeting officers’ social welfare thereby boosting performance of national police service projects in the police service in the area of study. The study recommended that the government need to periodically subject police officers in Nyeri County to training on security, investigation matters and trauma management, the National Police Commission should champion for improved welfare for police officers to escalate morale and consequently  performance of  national police service projects, and that there is need for National Police Commission to improve the working conditions of police officers in terms of  trauma management ,working relationship, occupational tenure, and officers safety.Key Words: Project Performance, Human Resources, Technological Resources, Monetary or Material Resources.